Kodaeral v Surabaya to Achieve Food Security in Support of the Indonesian Navy’s Duties - Eko Sulistyo Hadi; Hendrik Kurniawan; Ado Andika; Ahmad Faisol; Maha Al Nasser (Yayasan Adra Karima Hubbi, 2026)
Background. Food security is a critical issue in Indonesia, where the Navy possesses logistical infrastructure suitable for distribution but faces significant legal and institutional barriers. The Kodaeral v Surabaya case exemplifies legal ambiguities that limit the Navy’s involvement in non-traditional security sectors. Purpose. This study aims to analyze how existing legal frameworks can be restructured to formalize and integrate the Indonesian Navy’s role into the national food security strategy, especially during emergencies. Method. A qualitative approach was employed, combining the legal analysis of court rulings and policy documents with interviews with defense and food security experts. Results. The findings indicate that the absence of a formal legal mandate limits the Navy’s operational capacity in food security operations, despite its established logistical capabilities. Conclusion. Legal reforms are necessary to integrate the Navy into national resilience strategies, enabling a comprehensive approach that enhances their contribution to national welfare.